PUSAT KEGIATAN MAHASISWA UNIVERSITAS TANJUNGPURA - Maulana, Muhammad Adji; Purnomo, Yudi; Pebriano, Valentinus (JMARS: Jurnal Mosaik Arsitektur, 2024)
Currently, the Student Activity Center (Pusgiwa) in Tanjungpura University faces both physical (structural) and non-physical (user habit) issues that makes the Pusgiwa area ineffective for student activities. The facilities are inadequate and misused. This final project aims to design a more adequate Student Activity Center for Untan students, incorporating an open concept while considering contextual aspects and the physical and non-physical issues experienced in the previous design. The design methodology employed is Richard Whitaker's eight-step design process, encompassing five steps in design and three post-design steps. Richard Whitaker's five design steps include initiation, definition, preparation, analysis, and synthesis. The three post-design steps consist of temporal evaluation, alternative solution evaluation, and final reevaluation. The outcome of the design is an open Pusgiwa area that fulfills the student"™s activities needs. The new design addresses both the physical and non-physical issues found in the old Pusgiwa, providing facilities that better suit the needs of Untan students and a system accommodating the habits of the users, including security, cleanliness, and access for student fundraising efforts. The open design is implemented to foster a sense of community and place for students without compromising the primary function of the Pusgiwa area as a student activity zone.